2017
DOI: 10.17516/1997-1397-2017-10-2-216-222
|View full text |Cite
|
Sign up to set email alerts
|

Kolmogorov System with Explicit Hyperbolic Limit Cycle

Abstract: A class of Kolmogorov differential system is introduced.We show that under suitable assumptions on parameters, an algebraic hyprbolic limit cycle can occur, the explicit expression of this limit cycle is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Later on many other papers have been published providing explicit non-algebraic limit cycles for several polynomial differential systems, but in all these papers the explicit non-algebraic limit cycles are for polynomial differential systems of degree larger than or equal to 3, see [6,7,8,9,10,11,12,13,15,16], the authors of these papers are Aziza, Bendjeddou, Benterki, Benyoucef, Berbache, Boukoucha, Boukoucha, Cheurfa, Grazem and Salhi.…”
Section: Algebraic Limit Cycles Of Discontinuous Piecewise Linear Dif...mentioning
confidence: 99%
“…Later on many other papers have been published providing explicit non-algebraic limit cycles for several polynomial differential systems, but in all these papers the explicit non-algebraic limit cycles are for polynomial differential systems of degree larger than or equal to 3, see [6,7,8,9,10,11,12,13,15,16], the authors of these papers are Aziza, Bendjeddou, Benterki, Benyoucef, Berbache, Boukoucha, Boukoucha, Cheurfa, Grazem and Salhi.…”
Section: Algebraic Limit Cycles Of Discontinuous Piecewise Linear Dif...mentioning
confidence: 99%
“…For instance, Bendjeddou, Cheurfa and Berbache in [2] showed that the quartic system admits the circle as an invariant curve which corresponds of course to the limit cycle. In the same context, Benyoucef and Bendjeddou studied in [7,8] two polynomial systems of any degrees. They showed in the first paper that the considered system can admit up to four algebraic limit cycles in the plane and in the second one the system can admit a unique algebraic limit cycle in the first quadrant.…”
Section: Introductionmentioning
confidence: 99%